LEGALITAS RIWAYAT ASBÄB AL-NUZÅªL Telaah historis konteks turunnya ayat al-Quran - Kholid, Abd (TEOLOGIA, 2013)
Abstract: AsbÄb al-NuzÅ«l (occasions of revelation) is event becoming background send down the verse ofÂ the Quran. Scope solution of AsbÄb al-NuzÅ«l only relating to event degrading of the verse ofÂ the Quran especially in event relation and word expression, that include texts or materials. This science is very importance in order to interpret the verses of the Quran. This is not mean that it is to generalize interpretation entire verses of the Quran with AsbÄb al-NuzÅ«l, because there is not all verses of the Quran send down with AsbÄb al-NuzÅ«l. But, for the verses of the Quran have AsbÄb al-NuzÅ«l, that its interpretation is more authentic. Abstrak: AsbÄb al-NuzÅ«lÂ adalah peristiwa yang menjadi latar belakang turunnya ayat al-Quran. Ruang lingkup pembahasan AsbÄb al-NuzÅ«l hanya berkaitan dengan peristiwa diturunÂkannya ayat al-Quran terutama dalam hubungan peristiwa dan ungkapan kata, baik teks ayat, maupun redaksi ayat.Ilmu ini sangat penting dalam rangka menafsirkan ayat-ayat al-Quran.Hal ini bukan berarti menggeneralisasi keharusan menafsirkan seluruh ayat al-Quran dengan AsbÄb al-NuzÅ«l, karena tidak semua ayat al-Quran turun disertai dengan AsbÄb al-NuzÅ«l. Akan tetapi bagi ayat-ayat al-Quran yang memiliki AsbÄb al-NuzÅ«l, maka penafsirannya akan lebih otentik. Keywords: asbÄb al-nuzÅ«l, âulÅ«m al-QurâÄn, ilmu MaâÄnÄ« dan Ilmu BayÄn, Nabi Muá¸¥ammad, dan sahabat.